Fusion‐protein‐assisted protein crystallization. Issue 7 (1st July 2015) - Kobe, Bostjan; Ve, Thomas; Williams, Simon J.
<x xml:space="preserve">Abstract</x> Fusion proteins can be used directly in protein crystallization to assist crystallization in at least two different ways. In one approach, the `heterologous fusion‐protein approach', the fusion partner can provide additional surface area to promote crystal contact formation. In another approach, the `fusion of interacting proteins approach', protein assemblies can be stabilized by covalently linking the interacting partners. The linker connecting the proteins plays different roles in the two applications: in the first approach a rigid linker is required to reduce conformational heterogeneity; in the second, conversely, a flexible linker is required that allows the native interaction between the fused proteins. The two approaches can also be combined. The recent applications of fusion‐protein technology in protein crystallization from the work of our own and other laboratories are briefly reviewed.